Characterization of a novel and potentially lethal designer drug (±)‐cis‐para‐methyl‐4‐methylaminorex (4, 4'‐DMAR, or 'Serotoni'). Issue 7 (19th May 2014) - Brandt, Simon D.; Baumann, Michael H.; Partilla, John S.; Kavanagh, Pierce V.; Power, John D.; Talbot, Brian; Twamley, Brendan; Mahony, Olivia; O'Brien, John; Elliott, Simon P.; Archer, Roland P.; Patrick, Julian; et al.
<x xml:space="preserve">Abstract</x> During the second half of 2013, a total of 26 deaths involving para‐methyl‐4‐methylaminorex (4, 4'‐DMAR) were reported to the European Monitoring Centre for Drugs and Drug Addiction. While aminorex and 4‐methylaminorex (4‐MAR) are known psychostimulants, nothing is known about the comparatively new para‐methyl analog. Analytical characterization of two independent samples obtained from online vendors confirmed the presence of the (±)‐cis isomer that also appeared to be associated with at least 18 of the 26 deaths. Extensive characterizations included crystal structure analysis, single, tandem, and high‐resolution mass spectrometry, liquid and gas chromatography, and nuclear magnetic resonance spectroscopy. For the work described here, both the (±)‐cis and (±)‐trans racemates were also synthesized, confirming that the differentiation between these two forms was straight‐forward. Monoamine transporter activity was studied using rat brain synaptosomes which included the comparison with d‐amphetamine, aminorex and (±)‐cis‐4‐MAR. (±)‐cis‐4, 4'‐DMAR was a potent, efficacious substrate‐type releaser at transporters for dopamine, norepinephrine and serotonin with EC50 values of 8.6 ± 1.1 nM (DAT), 26.9 ± 5.9 nM (NET) and 18.5 ± 2.8 nM (SERT), respectively. The potency of (±)‐cis‐4, 4′‐DMAR at DAT and NET rivalled that of other psychomotor stimulant drugs like d‐amphetamine and aminorex. However, (±)‐cis‐4, 4′‐DMAR had much more potent actions at SERT and activity at SERT varied more than 100‐fold across the four drugs. The potent releasing activity of (±)‐cis‐4, 4′‐DMAR at all three monoamine transporters predicts a potential for serious side‐effects such as psychotic symptoms, agitation, hyperthermia and cardiovascular stimulation, especially after high‐dose exposure or following combination with other psychostimulants. Copyright © 2014 John Wiley & Sons, Ltd.